Investigation of some genetic variations in BMP15 accompanied with premature ovarian failure (POF) in Syrian women - Rana Al-ajoury; Essam Kassem; Bassel Al-halabi; Faten Moassess; Walid Al-achkar (Middle East Fertility Society Journal, 2015)
Background: Premature ovarian failure (POF) is a primary ovarian defect characterized by absent menarche or premature depletion of ovarian follicles. Bone morphogenetic protein 15 (BMP15) is an oocyte-derived growth factor acting as a major player in follicle differentiation in mammals. Mutations in this gene, lead to defective secretion of bioactive dimmers. The present study was to verify the involvement of BMP15 variations in POF women in Syria. Results: Genetic screening of 65 patients with POF, 55 primary amenorrhea (PA), 10 secondary amenorrhea (SA) and 100 controls of Syrian origin was done. Five variants in six patients were observed, including two missense substitutions: p. N103S (308A > G), p. A180T (538G > A), one silent variation p.S284S (852C > T), one insertion of three nucleotides (788 insTCT), and one novel intronic variant c. (851 + 13G > A). Variant (308A > G) was observed at the heterozygous state in one patient, variant (538G > A) was found at the heterozygous state in another patient, variant (852C > T) was identified in four patients: two patients at the heterozygous, the third patient had the variant (852C > T) associated with the insertion of three nucleotides [788insTCT]/(+)[852C > T]. This compound variant was detected for the first time in our study, and the fourth patient who had the variant (852C > T) was associated with novel intronic variant (851 + 13G > A) [851 + 13G > A](+)[852C > T]. In our controls the variant (852C > T), was observed in three controls, but the variant (308A > G) was detected in one control. Conclusion: Several data indicate that POF has a strong genetic component; these findings are consistent with the critical role played by BMP15 in human folliculogenesis.